A facile approach to synthesize graphitic carbon nitride microwires for enhanced photocatalytic H2 evolution from water splitting under full solar spectrum. Issue 14 (29th June 2018) - Dou, Hailong; Long, Dan; Zheng, Shaohui; Zhang, Yongping
Abstract : Photocatalytic hydrogen evolution from water splitting. Abstract : In this study, we fabricated porous fiber-like g-C3 N4 photocatalysts by calcifying melamine to improve the photocatalytic hydrogen evolution performance via a facile supramolecular hydrogel approach. The as-prepared g-C3 N4 microwire (MW(III)) photocatalysts significantly enhanced hydrogen production under solar irradiation (16.88 μmol h −1 ). The performances of photocatalysts fabricated from the same precursor via calcification improved with the increase in the crystallinity and the degree of polymerization. The use of different precursors led to variations in crystallinity, but H2 production was correlated with the crystallinity of the photocatalysts synthesized from the same precursor with a similar trend. This study provides a novel strategy to synthesize metal-free g-C3 N4 photocatalysts via increasing the crystallinity and degree of polymerization.